Interphase-arrested Drosophila embryos activate zygotic gene expression and initiate mid-blastula transition events at a low nuclear-cytoplasmic ratio - Strong, Isaac J. T. (PLoS Biol, 2020)
Externally deposited eggs begin development with an immense cytoplasm and a single overwhelmed nucleus. Rapid mitotic cycles restore normality as the ratio of nuclei to cytoplasm (N/C) increases. A threshold N/C has been widely proposed to activate zygotic genome transcription and onset of morphogenesis at the mid-blastula transition (MBT). To test whether a threshold N/C is required for these events, we blocked N/C increase by down-regulating cyclin/Cdk1 to arrest early cell cycles in Drosophila. Embryos that were arrested two cell cycles prior to the normal MBT activated widespread transcription of the zygotic genome including genes previously described as N/C dependent. Zygotic transcription of these genes largely retained features of their regulation in space and time. Furthermore, zygotically regulated post-MBT events such as cellularization and gastrulation movements occurred in these cell cycle–arrested embryos. These results are not compatible with models suggesting that these MBT events are directly coupled to N/C. Cyclin/Cdk1 activity normally declines in tight association with increasing N/C and is regulated by N/C. By experimentally promoting the decrease in cyclin/Cdk1, we uncoupled MBT from N/C increase, arguing that N/C-guided down-regulation of cyclin/Cdk1 is sufficient for genome activation and MBT.